EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN CANVA TERHADAP PENINGKATAN KREATIVITAS PESERTA DIDIK - wina Fauziah; Odang Hermanto; Prima Melati (Institut Pendidikan Indonesia, 2025)
The rapid development of digital technology today encourages the importance of increasing student creativity, one of which is through the implementation of the Project Based Learning model. This research aims to analyze the effectiveness of using the PjBL model with the help of Canva in increasing student creativity in making poster projects in Pancasila Education subjects in class XI SMAN 11 Garut. The research method used was a quasi-experimental with two groups: an experimental group using Canva-assisted PjBL and a control group using a conventional PjBL model. Data is collected through creativity tests before and after treatment and analysis of student poster work. Hypothesis test is done with independent sample t-test, paired sample t-test, and n-gain analysis to measure the increase in student creativity. Research results show that the use of Canva-assisted PjBL is effective in increasing student creativity. The independent sample t-test showed a significance value of 0.01 (< 0.05), which showed a significant difference between the experimental and control groups. The experimental group experienced a significant increase, while the control group did not. The n-gain result showed that the experimental class received a score of 0.41 (medium category), while the control received a score of -1,1595 (ineffective category). Keywords : Project Based Learning, Canva, Student’s Creativity